2011
DOI: 10.1021/jz2004655
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Nanosheets that Gel: Exfoliated Layered Double Hydroxides in Toluene

Abstract: A simple strategy to exfoliate inorganic layered double hydroxide (LDH) solids to their ultimate constituent, intact single layers of nanometer thickness and micrometer size, is presented. The procedure involves intercalation of an ionic surfactant that forms a hydrophobic anchored surfactant bilayer in the galleries of the solid followed by simply stirring the intercalated solid in toluene. The method is rapid but at the same time gentle enough to produce exfoliated nanosheets of regular morphology that are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 40 publications
1
61
0
1
Order By: Relevance
“…[20,21] Besides the sporadic reports on the direct synthesis of single-or multiple-layered protonated titanate nanosheets, [18,22] traditional alkaline hydrothermal methods usually result in alkali metal titanates with one-dimensional (1D) structures (for example, nanotubes, nanobelts, and nanorods), [23][24][25] which require an additional ion-exchange step to transform to their protonated forms. On the other hand, intercalation and exfoliation of lamellar compounds have been a classic research topic in inorganic and materials chemistry, [26][27][28] and single-layered titanate nanosheets have already been synthesized through a "top-down" approach. [29,30] However, constructing different hierarchical structures with low-dimensional building blocks through a "bottom-up" approach still remains as a great challenge for protonated titanates.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Besides the sporadic reports on the direct synthesis of single-or multiple-layered protonated titanate nanosheets, [18,22] traditional alkaline hydrothermal methods usually result in alkali metal titanates with one-dimensional (1D) structures (for example, nanotubes, nanobelts, and nanorods), [23][24][25] which require an additional ion-exchange step to transform to their protonated forms. On the other hand, intercalation and exfoliation of lamellar compounds have been a classic research topic in inorganic and materials chemistry, [26][27][28] and single-layered titanate nanosheets have already been synthesized through a "top-down" approach. [29,30] However, constructing different hierarchical structures with low-dimensional building blocks through a "bottom-up" approach still remains as a great challenge for protonated titanates.…”
Section: Introductionmentioning
confidence: 99%
“…These results clearly indicate that the dispersion of the LDH gel in xylene results in delamination of the LDHs to their ultimate constituents. Recently, Naik et al proposed that gel formation in surfactant‐anchored LDHs is a result of the attractive dispersive interactions of toluene with dodecyl sulfate chains anchored to opposing LDH sheets . O'Hare and co‐workers reported a gel‐like suspension for surfactant‐anchored Mg‐Al LDH synthesized by the reverse microemulsion method .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Naik et al proposed that gel formation in surfactant-anchored LDHs is a result of the attractive dispersive interactions of toluene with dodecyl sulfate chains anchored to opposing LDH sheets. 28,29 O'Hare and co-workers reported a gel-like suspension for surfactant-anchored Mg-Al LDH synthesized by the reverse microemulsion method. 30 Wu et al demonstrated gel formation in LDH-NO 3 in formamide without incorporation of surfactants.…”
Section: Resultsmentioning
confidence: 99%
“…22 Analogous systems in which the bivalent metal is Co, Ni or Zn were also delaminated in toluene. 23,24 The delamination of Mg-Al-glycine in formamide was reported in 2001. 25 Many other combinations of amino acid/polar solvent were tested, but only with glycine/formamide nearly exfoliated structures were obtained.…”
Section: Preparationmentioning
confidence: 99%